Income and campus application disparities among European and non-European heritage Hispanic undergraduate applicants - AJ Alvero; Sonia Giebel; Francis A. Pearman (PNAS Nexus, 2024)
Leveraging every undergraduate application submitted by self-identified Hispanic applicants to the University of California system in the 2016 and 2017 application cycles, we show that a significant number of applicants claim Hispanic identity by virtue of European heritage. We subsequently demonstrate that Hispanic-identifying students of European descent are significantly more affluent and more likely to apply to selective University of California campuses than their non-European Hispanic peers. We comment on the practical implications of these disparities, as well as their relevance for studies of inequality in the social sciences and education.
https://doi.org/10.7910/DVN/RZCS36
Keywords: 300; Hispanic; college admissions; disaggregation; ethnicity